OPTIMIZING PHYSICAL FITNESS OUTCOMES: THE IMPACT OF STRUCTURED PHYSICAL EDUCATION CURRICULA IN SCHOOLS - Junaid Hamid Bhat; Vijay Kumar (RADJA PUBLIKA, 2025)
In an era characterized by increasing sedentary behaviours and rising childhood obesity rates, the role of school based physical education (PE) has never been more pivotal. This paper examines how structured physical education curricula within schools can optimize physical fitness outcomes for students. Drawing on existing research and frameworks, the study explores the key components of effective PE curricula, mechanisms by which they influence physical fitness, implementation challenges, and policy implications. The evidence indicates that when PE curricula are thoughtfully designed incorporating consistent frequency, diversity of activities, fitness oriented objectives, and alignment with health literacy they contribute to enhanced cardiovascular fitness, muscular strength, bone health and motor skills. However, achieving these outcomes requires appropriate resources, trained educators, and system level support. The paper concludes with recommendations for educators, administrators and policymakers to maximize the benefits of PE within the school context.